Pengembangan Model Pembelajaran PDC (Preparing, Doing, Concluding) untuk Pembelajaran IPA - Reni Nurhapsari; Sutarto Sutarto; I Ketut Mahardika (Jurnal Pembelajaran dan Pendidikan Sains, 2016)
This study aims to describe PDC (Preparing, Doing, Concluding) model that valid for science learning in junior high School. The study is a developmental research. The research uses Borg and Gall model, that conducted to students class VIII SMPN 2 Umbulsari even semester year 2015-2016. Validity of the model is determined by the score validity of characteristics model, learning tools with using the model by science learning experts and practiciants (science teachers). Validity the model is also determined by questionnaire score to the model and obtained by students and teachers’ responses about the implementation of the model in learning process. Findings of the study are: (1) the average validity value of experts and users about model characteristics and learning tools are 84.18% (very valid) and 80,76% (valid) respectively; (2) the validity score of the questionnaire about the model is 80.47% (valid); and (3) teachers’ responses as user validity and students’ responses as audience validity to implementation the model are 82,71% (very valid) and 82.06% (very valid). Respectively. So, the research can be concluded that PDC model with its characters (syntax, social system, reaction principle, supporting system, and instructional and nurturant system) is valid for science learning in junior high school.